Design of CSP plants with optimally operated thermal storage. (June 2015) - Casati, E.; Casella, F.; Colonna, P.
Highlights: Methodology presented to assess the potential of thermal storage optimal operation. Average gain in yearly revenue around 5% obtained with respect to usually adopted short-sighted strategies. Above figure amplified to more than 10% in terms of net present value of the investment. Unveiled also potential of optimal control in terms of investment cost reduction. Operation strategy constitutes a new important design variable for CSP systems with storage. Abstract: Concentrated solar power plants are increasingly considered worldwide, in order to meet the demand for renewable power generation. A distinctive feature of these plants is the possibility of integrating thermal energy storage such that full-load operation can be sustained for several hours in the absence of solar radiation. A number of design software tools are available for sizing the plant and evaluating the return on investment. These usually assume a short-sighted strategy for storage management. This work presents a new methodology aimed at assessing the potential of optimal control techniques when applied to the operation of energy storage systems in general. The design method is applied to a test case, a state-of-the-art central receiver plant with direct storage, using molten salts as working fluid, and operating in a context of variable electricity prices. The system modeling and optimization problems are formulated and implemented using modern high-level modeling languages, demonstrating the potential of the approach. The different operating strategies are compared based on a detailed financial analysis. A wide system design space is explored, and the results presented for all the foreseeable combinations of solar field size and storage system capacity, considering two plant locations, i.e., Daggett (US-CA) and Almeria (ES). Potential gains up to 10% in terms of yearly revenue are estimated, in case improved control strategies are adopted. These figures translate into increases of more than 30% of the investment profitability by considering over-life financial figures. It is further shown how, in case of state-of-the-art systems, it is always profitable to adopt optimal control to the end of increasing electricity production. However, the potential of these techniques is discussed also under the point of view of investment cost reduction, since the same yearly revenue can be harvested with smaller energy storage, if optimally operated. This aspect, unveiled here for the first time, might become significant if technologies with different cost structure are of interest, i.e., in case the storage cost constitutes a comparatively large part of the total investment. The novel method is thus an additional decision tool allowing to treat the storage operation strategy as a new relevant variable for the design of next generation energy systems.